Zařízení pro diagnostiku asynchronních motorů - Bulín, Tomáš; Ondrůšek, Čestmír; Huzlík, Rostislav (International Society for Science and Engineering, o.s., 2016)
The aim of this article is to introduce the faults of induction machines and design of a device for their detection. It is appropriate to detect occurring fault to prevent greater damage in industrial production. Monitoring can be performed by various types of methods, but the stator currents are going to be measured preferentially in this article. Test measuring device, which was created, consists of a current sensors and hardware from National Instruments. Control is realized using LabVIEW, which performs data collection, processing, and evaluation.

Cílem tohoto článku je seznámit se s poruchami asynchronních motorů a navržením zařízení pro jejich detekování. V průmyslové výrobě je vhodné včas odhalit vznikající poruchu, aby nedošlo k větším škodám. Provádět monitorování lze různými typy metod, ale podrobněji se budeme zabývat pouze měřením statorových proudů. Vytvořené testovací měřicí zařízení se skládá z proudových čidel a hardwaru od National Instruments. Ovládání zařízení je realizováno za pomoci programu LabVIEW, kde se provádí sběr dat, jejich zpracování a vyhodnocení.
Device for diagnostics of induction machine